The Maintenance of Bahasa Banjar in Langkat - Neneng sri lestari neneng; Edi Suprayetno (LPPM STKIP AL MAKSUM, 2023)
This study deals with the maintenance of bahasa Banjar in Langkat. It employs qualitative research design. This study aims to describe the maintenance of bahasa Banjar in Langkat. The subjects were twenty Banjarnese speakers in Langkat. The instruments used for this study were observation, questionnaire, and interview (in-depth interview). The observation was applied to get the data about the Banjarnese speakers in maintaining their language such what the language that they used in daily communication. Questionnaire was applied to collect the data about the factors which support bahasa Banjar maintenance in Langkat and interview was applied to get data about the reason of Banjarnese to maintain their language and to get in depht result of the research. The data was analyzed by using Miles and Huberman’s data analysis. bahasa Banjar is maintained in Langkat. They keep using their language (bahasa Banjar) in Langkat because they realize the condition of bahasa Banjar nowdays, whereas there were some of them shift from bahasa Banjar maintenance. They are living in an area dominated by Banjarnese, visiting homeland regularly, intra marriage, use of the language in family domain, use of the language in neighborhood domain, use of the language in workplace domain, use the language in education domain, ethno linguistic vitality, use of the languge in religion domain, practice of adat istiadat (traditional) ceremony and solidarity of Banjarnese to use their language together. bahasa Banjar keep maintain and exist in Langkat. Keywords: Maintenance, Bahasa Banjar